IMPLEMENTATION OF SOLAR FRIDGE WITH FAST CHILLING APPLICATIONS WITH VOLTAGE MONITORING (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In this paper we are mainly focusing on a solution to control this problem we have focused on refrigerators which releases CFC’s. Here we are designing a mini solar based refrigerator which is cheaper as well as eco-friendly. Here we are using Micro controller (AT89S52) allows dynamic and faster control. Liquid crystal display (LCD) makes the system user-friendly. In this paper we are using solar panels for charging a Lead Acid Battery (12V, 1.2 Amp hrs), a pelteir thermoelectric device when connected to battery generates cool effect and hot effects depending on the mode required by the user. Since we are using this for fridge we need only cool mode. A peltier thermoelectric device is connected to the battery to generate cooling effect..We need to display the voltage for that we are using ADC0808 which is given to the controller. For this ADC we are giving a clock pulses through 555 timer to perform its operation. This paper uses regulated 5V; 500mA power supply. A 7805 three terminal voltage regulator is used for voltage regulation. Bridge type full wave rectifier is used to rectify the ac output of secondary of 230/12V step down transformer.